Ulcer-like Co-doped Ni3S2 electrode material, its preparation method and application
Patent Information
- Application Number
- CN202310642139.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-31
AI Technical Summary
电解水过程包括析氢反应(HER)和析氧反应(OER),由于OER为多步四电子转移过程,限制了水裂解的速率,因此需要开发高效的OER电催化剂来克服高动力学阻力
[0012]在海胆状的外形结构以及材料中电子的偏移的协同作用下,极大地提升了电极材料的OER催化性能,并在100mA cm-2大电流密度下能够持续48h,表现出优异的稳定性。本申请所制备的电极材料,在碱性环境中表现出非常优异的OER电催化性能,10mA cm-2高电流密度下的过电位仅为235mV。Tafel斜率值仅有45.7mV dec-1,电荷转移电阻仅为1.25Ω,均低于同种工艺下未掺杂Co离子的Ni3S2。
Smart Images

Figure CN116770350B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a sea urchin-shaped Co-doped Ni3S2 electrode material, its preparation method, and its application, belonging to the field of electrode material preparation technology. Background Technology
[0002] Hydrogen (H2) is an important energy source, characterized by its environmental friendliness and recyclability. Water splitting technology is currently one of the main sources of hydrogen. The water electrolysis process includes the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Since the OER is a multi-step four-electron transfer process, it limits the rate of water splitting. Therefore, it is necessary to develop highly efficient OER electrocatalysts to overcome the high kinetic resistance. Generally, noble metals and their derivatives (such as IrO2 and RuO2) are excellent OER electrocatalysts, but their high cost and low stability limit their practical application. Developing high-performance, non-noble metal OER electrocatalysts has become an important research topic.
[0003] In recent years, transition metal sulfides have attracted much attention due to their excellent electrical conductivity and high catalytic activity. Among these catalysts, nickel sulfides are considered promising candidates for OER electrocatalysts due to their superior electrical conductivity and good electrocatalytic activity. Especially for Ni3S2, further research is needed to improve the activity and stability of the electrocatalyst. Summary of the Invention
[0004] To improve the activity and stability of Ni3S2 as an electrocatalyst, this application first discloses a method for preparing a sea urchin-like Co-doped Ni3S2 electrode material, which includes the following steps:
[0005] (1) Pretreatment of nickel foam: The nickel foam was ultrasonically treated in hydrochloric acid to remove the oxide film on the surface of the nickel foam. Then, it was ultrasonically treated in acetone, anhydrous ethanol and deionized water in sequence, and then vacuum dried to obtain pretreated nickel foam for later use.
[0006] (2) Electrode material preparation: Electrode material was prepared by electrodeposition using a three-electrode system. Specifically, thiourea, nickel chloride hexahydrate and cobalt chloride hexahydrate were dissolved in deionized water and stirred evenly to form a transparent solution as the electrolyte. Pretreated nickel foam was used as the working electrode, Pt sheet electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition reaction was carried out by cyclic voltammetry.
[0007] After the electrodeposition reaction is completed, a primary doped electrode material is obtained. The primary doped electrode material is then cleaned and vacuum dried to obtain a Co-doped Ni3S2 electrode material.
[0008] In step (1), when the nickel foam is ultrasonically treated in hydrochloric acid, acetone, anhydrous ethanol and deionized water, the ultrasonic time is controlled within 10 to 30 minutes respectively. When vacuum drying, the temperature is 50 to 70°C and the time is 3 to 5 hours.
[0009] In step (2), after dissolving thiourea, nickel chloride hexahydrate and cobalt chloride hexahydrate in deionized water, the solution is stirred for 20 to 50 minutes to make it uniform; when cleaning the initial sample of doped electrode material, deionized water and anhydrous ethanol are used alternately for 2 to 5 cleanings.
[0010] In this application, to improve the conductivity of Ni3S2, Co was selected for electrodeposition to dope Ni3S2, which can adjust the electronic structure of the material. During the Co doping process, Co ions replace part of the Ni element in the Ni3S2 structure. In this application, the molar ratio of Co to Ni is 4-6%. Under the attraction of Co ions, some electron pairs in the Ni-S bond move closer to Co, thereby reducing the electron density near Ni and obtaining Ni with a higher valence state, thus improving the activity of the catalytic active sites. At the same time, the material prepared by electrodeposition has a disordered amorphous structure with a sea urchin-like nanosphere structure, which significantly increases the specific surface area of the material and exposes more catalytic active sites. The electrode material obtained by this process has more exposed active sites and excellent conductivity, thereby improving the OER electrocatalytic performance of the material.
[0011] Since the electrode material in this application has a disordered amorphous structure, it can effectively improve its catalytic activity. The electrocatalytic reaction is a surface chemical reaction, which preferentially occurs at catalytic active sites or surface defect sites. The amorphous phase has the characteristics of short-range order and long-range disorder, and has a high density of catalytic active sites and conductivity.
[0012] The synergistic effect of the urchin-like morphology and the electron shift within the material significantly enhances the OER catalytic performance of the electrode material, achieving a peak performance at 100 mA cm⁻¹. -2 It can withstand high current density for 48 hours, exhibiting excellent stability. The electrode material prepared in this application demonstrates excellent OER electrocatalytic performance in an alkaline environment, at 10 mA cm⁻¹. -2 The overpotential at high current density is only 235mV. The Tafel slope is only 45.7mV dec. -1 The charge transfer resistance is only 1.25Ω, which is lower than that of Ni3S2 without Co ions under the same process.
[0013] This application uses transition metal sulfide catalysts instead of commonly used noble metal oxides, which greatly reduces the cost of the catalyst. The prepared Co-doped Ni3S2 electrode material has low overpotential, strong conductivity, excellent catalytic performance and good stability, and is expected to be widely used in the field of electrocatalytic oxygen production.
[0014] In addition, the technology provided by this invention does not produce polluting gases in reactions involving sulfur sources, is environmentally friendly, has a short reaction time, excellent catalytic performance and stability, and is low in cost.
[0015] Specifically, in order to ensure the doping ratio of Co ions and improve the activity of the catalytic active sites of the material, the concentration of cobalt chloride hexahydrate is 1-10 mmol / L, the concentration of thiourea is 450-550 mmol / L, and the concentration of nickel chloride hexahydrate is 45-55 mmol / L.
[0016] Specifically, the voltage range of the cyclic voltammetry is -1.2V to 0.2V, and the scan rate is 10 to 100mV / s. Based on the deposition potentials of Ni and S ions, Co-ion Ni3S2 can be successfully prepared under these conditions. The scan rate of 10 to 100mV / s is chosen because a suitable deposition rate can yield a uniformly distributed material.
[0017] Specifically, the number of electrodeposition cycles is 30 to 60. The number of cycles determines the deposition time. Excessive electrodeposition time will lead to material buildup, reducing the specific surface area and thus reducing the exposure of active sites. Shorter electrodeposition time will also reduce the exposure of active sites, thus affecting electrocatalytic performance.
[0018] Specifically, in step (2), when the doped electrode material is vacuum dried, the temperature is 50-80℃ and the time is 10-20h.
[0019] Specifically, in step (1), the concentration of hydrochloric acid is 1-3 mol / L. In order to obtain smooth and clean nickel foam, it is necessary to pretreat with hydrochloric acid of appropriate concentration. If the concentration of hydrochloric acid is too low, the pretreatment will be incomplete, and if the concentration is too high, it will react too much with the nickel foam, affecting the conductivity of the final material.
[0020] Secondly, this application also discloses a sea urchin-shaped Co-doped Ni3S2 electrode material, which is prepared by any of the preparation methods described above.
[0021] The electrode material has a disordered amorphous structure, which can effectively improve its catalytic activity. The electrocatalytic reaction is a surface chemical reaction, which preferentially occurs at catalytic active sites or surface defect sites. The amorphous phase has the characteristics of short-range order and long-range disorder, and has a high density of catalytic active sites and conductivity. The electrode material also has a sea urchin-like morphological structure.
[0022] The synergistic effect of the urchin-like morphology and the electron shift within the material significantly enhances the OER catalytic performance of the electrode material, achieving a peak performance at 100 mA cm⁻¹. -2 It can withstand high current density for 48 hours, exhibiting excellent stability. The electrode material prepared in this application demonstrates excellent OER electrocatalytic performance in an alkaline environment, at 10 mA / cm². -2 The overpotential at high current density is only 235mV. The Tafel slope is only 45.7mV dec. -1 The charge transfer resistance is only 1.25Ω, which is lower than that of Ni3S2 without Co ions under the same process.
[0023] Furthermore, this application also discloses the application of the aforementioned urchin-shaped Co-doped Ni3S2 electrode material in the electrocatalytic oxygen evolution reaction in an alkaline solution. Specifically, the alkaline solution is a KOH solution with a concentration of 1 mol / L. Attached Figure Description
[0024] Figure 1 The X-ray diffraction (XRD) patterns of the electrode materials obtained in Example 1 and Comparative Example 1 of this invention are shown for phase characterization.
[0025] Figure 2 The images shown are scanning electron microscope (SEM) images of the electrode materials obtained in Example 1 and Comparative Example 1 of this invention, for morphological characterization. Figure 2 (a) is a scanning electron microscope (SEM) image of the electrode material obtained in Example 1. Figure 2 (b) is a scanning electron microscope (SEM) image of the electrode material obtained in Comparative Example 1.
[0026] Figure 3 The LSV polarization curves of the electrode materials obtained in Example 1 and Comparative Example 1 of this invention characterize the electrocatalytic performance of OER.
[0027] Figure 4 The Tafel curves of the electrode materials obtained in Example 1 and Comparative Example 1 of this invention characterize the speed of OER kinetics.
[0028] Figure 5 The EIS curves of the electrode materials obtained in Example 1 and Comparative Example 1 of this invention characterize the charge transfer rate of the materials.
[0029] Figure 6 The it curve is the electrode material obtained in Example 1 of this invention, which characterizes the stability of the material. Detailed Implementation
[0030] Example 1:
[0031] (1) Pretreatment of nickel foam: Nickel foam cut into 2cm*4cm specifications was placed in dilute hydrochloric acid with a concentration of 3mol / L and ultrasonically treated for 15 minutes to remove the oxide layer on the surface of nickel foam. Then, it was ultrasonically treated for 15 minutes each in acetone, anhydrous ethanol and deionized water. Finally, the cleaned nickel foam was placed in a vacuum drying oven and vacuum dried for 4 hours at a pressure of -0.095MPa and a temperature of 60℃ to obtain pretreated nickel foam.
[0032] (2) Preparation of electrode materials: 5 mmol of nickel chloride hexahydrate, 50 mmol of thiourea and 0.3 mmol of cobalt chloride hexahydrate were dissolved in 100 mL of deionized water and stirred for 30 minutes to form a uniform and transparent solution, which was used as the electrolyte.
[0033] A three-electrode system was assembled, with pretreated nickel foam as the working electrode, a Pt sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode. Cyclic voltammetry was used to obtain a preliminary doped electrode material by 30 cycles at a voltage range of -1.2V to 0.2V (vs. Ag / AgCl) and a scan rate of 10mV / s. The preliminary doped electrode material was then alternately washed 6 times with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven and vacuum dried at a pressure of -0.095MPa and 60℃ for 12h to obtain Co-doped Ni3S2 electrode material.
[0034] Comparative Example 1:
[0035] Preparation of Ni3S2 electrode material:
[0036] (1) Pretreatment of nickel foam: Nickel foam cut into 2cm*4cm specifications was placed in dilute hydrochloric acid with a concentration of 3mol / L and ultrasonically treated for 15 minutes to remove the oxide layer on the surface of nickel foam. Then, it was ultrasonically treated for 15 minutes each in acetone, anhydrous ethanol and deionized water. Finally, the cleaned nickel foam was placed in a vacuum drying oven and vacuum dried at a pressure of -0.095MPa and 60℃ for 4 hours to obtain pretreated nickel foam.
[0037] (2) Preparation of electrode materials: 5 mmol of nickel chloride hexahydrate and 50 mmol of thiourea were dissolved in 100 mL of deionized water and stirred for 30 minutes to form a uniform and transparent solution, which was used as the electrolyte.
[0038] A three-electrode system was assembled, using pretreated nickel foam as the working electrode, a Pt sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode. Cyclic voltammetry was used to obtain a preliminary Ni3S2 electrode material by 30 cycles at a voltage range of -1.2V to 0.2V (vs. Ag / AgCl) and a scan rate of 10mV / s. The material was then washed six times alternately with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven at a pressure of -0.095MPa and a temperature of 60℃ for 12 hours to obtain the Ni3S2 electrode material.
[0039] Example 2:
[0040] Same as Example 1, except that the concentration of cobalt chloride hexahydrate is 1 mmol / L.
[0041] Example 3:
[0042] Same as Example 1, except that the concentration of cobalt chloride hexahydrate is 10 mmol / L.
[0043] The Co-doped Ni3S2 electrode material of Example 1 and the Ni3S2 electrode material of Comparative Example 1 were tested to obtain... Figure 1 The X-ray diffraction pattern shown is... Figure 1 NF in the text represents nickel foam, and Co-Ni3S2 represents Co-doped Ni3S2.
[0044] Figure 1 The results show that the samples prepared in Example 1 and Comparative Example 1 both exhibit standard Ni3S2 diffraction peaks (PDF#71-1682). Because they are loaded on nickel foam, they also exhibit standard Ni diffraction peaks (PDF#87-0712). It can be seen that the intensity of the Co-Ni3S2 diffraction peak is stronger than that of the Ni3S2 diffraction peak, and the corresponding diffraction peak shifts to a smaller angle. No other diffraction peaks appear, indicating that successful Co doping of Ni3S2 will affect the electronic structure of the electrode material, thereby improving the electrocatalytic activity. The Co-doped Ni3S2 electrode material was analyzed using an X-ray fluorescence spectrometer from Shimadzu Corporation, Japan, where the molar substitution ratio of Co to Ni was 5.28%.
[0045] Figure 2 (a) and (b) are SEM images of the Co-doped Ni3S2 electrode material of Example 1 and the Ni3S2 electrode material of Comparative Example 1, respectively. Figure 2 This indicates that undoped Ni3S2 exhibits a nanosheet structure, while Co-doped Ni3S2 exhibits regular sea urchin-shaped nanospheres, significantly increasing the specific surface area of the material, exposing more catalytic active sites, and thus benefiting electrocatalytic activity.
[0046] Electrocatalytic performance testing of electrode materials for OER: The electrocatalytic performance of OER was tested using a Shanghai Chenhua CHI760E electrochemical workstation at room temperature. A standard three-electrode system was used, with nickel foam carrying electrode materials as the working electrode, an Hg / HgO electrode as the reference electrode, and a Pt sheet as the counter electrode. The electrolyte used for the electrocatalytic test was a 1 mol / L KOH alkaline solution. Before testing the OER catalytic performance, the working electrode was activated using cyclic voltammetry to stabilize its performance. The voltage window was set to 0–1 V (vs. Hg / HgO), the scan rate was 100 mV / s, and the number of cycles was 60. After activation, the OER catalytic performance was evaluated by measuring the LSV polarization curve of the working electrode. The voltage window was set to 1–0 V (vs. Hg / HgO), and the scan rate was 5 mV / s.
[0047] Linear reverse scanning can avoid interference from oxidation peaks, yielding a more accurate overpotential for the OER. The potential in the obtained LSV polarization curve first needs to be converted to a potential relative to the reversible hydrogen electrode. The conversion formula is:
[0048] E(RHE)=E(Hg / HgO)+0.098+0.0592×pH,
[0049] Where E(RHE) is the potential relative to the reversible hydrogen electrode, E(Hg / HgO) is the measured potential, and pH is the pH value. Considering the voltage drop caused by ohmic polarization during electrocatalysis, ohmic compensation is also required for the potential in the LSV polarization curve. At an overpotential of 300 mV, 0.01–10 5 EIS testing was performed at Hz, 100mA cm -2 Stability tests were conducted using the it method at current density.
[0050] Figure 3 These are the LSV polarization curves of the Co-doped Ni3S2 electrode material in Example 1 and the Ni3S2 electrode material in Comparative Example 1. Figure 3 It can be seen that the performance of Co-doped Ni3S2 electrode material is significantly better than that of Ni3S2 electrode material at 10 mA cm⁻¹. -2 At the given current density, the overpotential of Co-doped Ni3S2 is only 235 mV, the overpotential of Ni3S2 is 264 mV, and the overpotential of pure nickel foam is 370 mV. In summary... Figures 1-3 Analysis suggests that the superior OER catalytic performance of the urchin-shaped Co-doped Ni3S2 electrode material stems from the increased number of exposed catalytic active sites due to the morphology, and the improved activity of these sites due to Co-doping-induced electronic structure regulation. Figure 3 In this context, Co-Ni3S2 is Co-doped Ni3S2.
[0051] Figure 4 These are the Tafel curves of the Co-doped Ni3S2 electrode material in Example 1 and the Ni3S2 electrode material in Comparative Example 1. The Tafel slope of Co-doped Ni3S2 is lower than that of Ni3S2 and pure NF, with a Tafel slope of only 45.7 mV dec. -1 The Tafel slopes for Ni3S2 and pure NF are 93.6 mV dec. -1 and 166.8mV dec -1 This indicates that Co-doped Ni3S2 exhibits relatively fast OER reaction kinetics. Figure 4 In this context, Co-Ni3S2 is Co-doped Ni3S2.
[0052] Figure 5 These are the EIS curves of the Co-doped Ni3S2 electrode material in Example 1 and the Ni3S2 electrode material in Comparative Example 1. It can be seen that the semi-circular radius of the Co-doped Ni3S2 is smaller than that of Ni3S2. The charge transfer resistance (Rct) of the Co-doped Ni3S2 is 1.25 Ω, while that of Ni3S2 is 1.75 Ω. This indicates that the Co-doped Ni3S2 has a faster charge transfer capability. Figure 5 In this context, Co-Ni3S2 is Co-doped Ni3S2.
[0053] Figure 6 This is the it curve of the electrode material prepared in Example 1. The results show that at 100 mA cm⁻¹... -2 It can operate stably for 48 hours under high current density, demonstrating excellent stability.
[0054] When the Co-doped Ni3S2 electrode materials obtained in Examples 2 and 3 were tested, the results were approximately the same as those in Example 1.
Claims
1. A method for preparing a sea urchin-shaped Co-doped Ni3S2 electrode material, characterized in that, Includes the following steps: (1) Pretreatment of nickel foam: The nickel foam was ultrasonically treated in hydrochloric acid to remove the oxide film on the surface of the nickel foam. Then it was ultrasonically treated in acetone, anhydrous ethanol and deionized water in sequence, and then vacuum dried to obtain pretreated nickel foam for later use. (2) Electrode material preparation: The electrode material was prepared by electrodeposition using a three-electrode system. Specifically, thiourea, nickel chloride hexahydrate and cobalt chloride hexahydrate were dissolved in deionized water and stirred evenly to form a transparent solution as the electrolyte. The concentration of cobalt chloride hexahydrate was 1-10 mmol / L, the concentration of thiourea was 450-550 mmol / L, and the concentration of nickel chloride hexahydrate was 45-55 mmol / L. Co ions partially replace Ni elements in the Ni3S2 structure in an ionic state, with a molar substitution ratio of 4-6% for Ni. Pretreated nickel foam was used as the working electrode, Pt sheet electrode as the counter electrode, and Ag / AgCl as the reference electrode. The electrodeposition reaction was carried out by cyclic voltammetry. The voltage range of the cyclic voltammetry was -1.2V to 0.2V, and the scan rate was 10 to 100 mV / s. After the electrodeposition reaction is completed, a primary doped electrode material is obtained. The primary doped electrode material is then cleaned and vacuum dried to obtain a Co-doped Ni3S2 electrode material.
2. The preparation method according to claim 1, characterized in that, The electrolyte contains cobalt chloride hexahydrate at a concentration of 3 mmol / L, thiourea at a concentration of 500 mmol / L, and nickel chloride hexahydrate at a concentration of 50 mmol / L. The cyclic voltammetry scan rate is 10 mV / s, and the number of cycles is 30.
3. The preparation method according to claim 1, characterized in that, In step (2), when the doped electrode material is vacuum dried, the temperature is 50-80℃ and the time is 10-20h.
4. The preparation method according to claim 1, characterized in that, In step (1), the concentration of hydrochloric acid is 1 to 3 mol / L.
5. A sea urchin-shaped Co-doped Ni3S2 electrode material, characterized in that, It is prepared by the preparation method described in any one of claims 1-4.
6. The application of the urchin-shaped Co-doped Ni3S2 electrode material according to claim 5 in the electrocatalytic oxygen evolution in alkaline solution.
7. The application according to claim 6, characterized in that, The alkaline solution is a KOH solution.
8. The application according to claim 7, characterized in that, The concentration of the alkaline solution is 1 mol / L.
Citation Information
Patent Citations
Efficient splitting water double functional electric catalyst and preparation method and application thereof
CN107469835A
Catalyst for producing hydrogen by electrolyzing water, preparation method and method for producing hydrogen by electrolyzing water
CN115874196A
